Legal analysis of the use of artificial intelligence systems in military operations carried out by the TNI reviewed from the principles of humanitarian law - Reynaldo Adi Putra; Tiarsen Buaton; Allan Hermit Prasetyo (Dynamics of Politics and Democracy, 2023)
Purpose: This study analyzes the application of artificial intelligence systems in military operations by the TNI by paying attention to the enforcement of humanitarian law principles. Research/methodology: The research method used is normative juridical with an analysis of applicable legal provisions which is carried out by reviewing and collecting legal documents and limited interviews with experts in their fields. Results: The conclusion of this study is that although artificial intelligence systems have great potential to influence the methods and tools in current and future military operations. The influence of artificial intelligence systems gives the system the authority to move on its own without any role from humans. Changes in the pattern of military operations require a clear legal framework and strict enforcement to ensure that their use by the TNI does not violate the principles of humanitarian law. Suggestions: This study suggests the need to develop more comprehensive national and international regulations to regulate the use of artificial intelligence systems in military operations carried out by the TNI in order to comply with the principles of humanitarian law.